Match injury incidence during the Super Rugby tournament is high: a prospective cohort study over five seasons involving 93 641 player-hours. Issue 10 (29th June 2018) - Schwellnus, Martin P; Jordaan, Esme; Janse van Rensburg, Charl; Bayne, Helen; Derman, Wayne; Readhead, Clint; Collins, Rob; Kourie, Alan; Suter, Jason; Strauss, Org
Abstract : Objectives: To determine the incidence and nature of injuries in the Super Rugby tournament over a 5-year period. Methods: 482 male professional rugby union players from six South African teams participating in the Super Rugby tournament were studied (1020 player-seasons). Medical staff of participating teams (2012–2016 tournaments) recorded all time loss injuries (total injuries and match injuries) and exposure hours (93 641 total playing hours; 8032 match hours). Injury incidence, injured player proportion, severity (time lost), anatomical location, tissue type and activity/phase during which injury occurred are reported. Results: The overall incidence of match injuries (per 1000 player-hours; 95% CI) for each year was as follows: 2012 (83.3; 69.4–99.2); 2013 (115.1; 98.7–133.5); 2014 (95.9; 80.8–113.1), 2015 (112.3; 96.6–129.9) and 2016 (93.2; 79.9–107.9). The injured player proportion for each year was as follows: 2012 (54.6%); 2013 (49.4%); 2014 (52.0%); 2015 (50.0%); and 2016 (39.8%). The thigh, knee, head/face and shoulder/clavicle are the most frequently injured locations, and muscle/tendon and joint/ligament injuries account for the majority of injuries. Most injuries (79%) occur in contact situations, in particular during a tackle (54%). Conclusion: The incidence of match injuries and the injured player proportion in South African teams competing in the Super Rugby tournament is high. Match injury incidence is consistently higher than previously reported for senior male rugby players at elite/professional level. Targeted risk management strategies are therefore needed in the Super Rugby tournament to manage risk of injury.